Juvenile Dermatomyositis (Medicine Today, 2016)
Juvenile dermatomyositis (JDM) is an autoimmune vasculopathy affecting children and adolescent under the age of 18 years. In this report, we describe a 9 years old boy who had myopathy and typical skin rash. Upon treatment with oral prednisolone and topical corticosteroid the patient condition considerably improved. Our case report illustrates that JDM requires comprehensive evaluation and multidisciplinary management.Medicine Today 2015 Vol.27(2): 46-48